2015
DOI: 10.1002/cssc.201501332
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanowire Top Electrodes in Flexible Perovskite Solar Cells using Titanium Metal as Substrate

Abstract: Flexible perovskite solar cells (FPSCs) have various applications such as wearable electronic textiles and portable devices. In this work, we demonstrate FPSCs on a titanium metal substrate employing solution-processed silver nanowires (Ag NWs) as the top electrode. The Ag NW electrodes were deposited on top of the spiro-MeOTAD hole transport layer by a carefully controlled spray-coating method at moderate temperatures. The power conversion efficiency (PCE) reached 7.45 % under AM 1.5 100 mW cm(-2) illuminatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
79
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 42 publications
0
79
0
3
Order By: Relevance
“…Early reports trying a solvent-based process in depositing MeNW-networks on the top of OMHP layers have already demonstrated that the selection of water and ethanol as a primary solvent truly degrades the underlying OMHP layer immediately upon the coating process. [90,92] Such a problem has been dealt with in various ways. The first of these is solvent optimization.…”
Section: Degradation Of Perovskite Layer By Polar Solventsmentioning
confidence: 99%
See 2 more Smart Citations
“…Early reports trying a solvent-based process in depositing MeNW-networks on the top of OMHP layers have already demonstrated that the selection of water and ethanol as a primary solvent truly degrades the underlying OMHP layer immediately upon the coating process. [90,92] Such a problem has been dealt with in various ways. The first of these is solvent optimization.…”
Section: Degradation Of Perovskite Layer By Polar Solventsmentioning
confidence: 99%
“…[15,129] Accordingly, several groups have made efforts to employ MeNW-network electrodes as a transparent electrode ( Table 2). [90,98,99,[130][131][132] Schematic illustrations of each type of PSC employing flexible MeNW-network electrodes are presented in Figure 6.…”
Section: Flexible Pscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrodes, including thin metallic films, 25,26 metal nanowires, 27 carbon nanotubes, 28 graphenes, 29 and transparent conductive oxides, 30 have been developed to replace these expensive sheets. We used a Au film as the semi-transparent electrode for perovskite-based bifacial solar cells.…”
mentioning
confidence: 99%
“…31 Several groups carried out experiments on metallic substrates. 32,33 Compared with using glass counterparts for conduction, metallic substrates have several advantages, such as the capability of withstanding higher temperatures, higher permeation barrier properties, and higher conductivity. 34 These metallic substrates include titanium substrate, 35 titanium fiber, 36 and stainless-steel fiber.…”
mentioning
confidence: 99%